Big Meeting - Daugharty, Janice (My University, 1990)
Daugharty, Janice. "Big Meeting," n.d. Series 2: The Short Stories (Unpublished), 2, Box: 5; Box: 6; Box: 7. Janice Daugharty Papers, MS-22. Valdosta State University Archives and Special Collections. Box 6, Folder 13.
Daugharty, Janice. "Big Meeting," n.d. 1 electronic record. 1 pdf document. 4 scans.
Keywords: Daugharty, Janice, 1944-; American literature--Women authors; Short stories